Estudo da vitamina D em pacientes com anemia falciforme: associação com biomarcadores não convencionais de lesão renal - Santos, Sandra Pereira dos (2024)
Sickle cell anemia (SCA) is an inherited disease characterized by a point mutation in the beta globin gene generating an abnormal hemoglobin (HbSS). Acute kidney injury (AKI) is often seen in PA.Vitamin D deficiency in this disease is associated with AKI. Since the kidney is the main organ involved in the production of bioactive forms of vitamin D, the existence of chronic kidney disease becomes an important risk factor for the development of vitamin D deficiency. Thus, the present study aimed to assess the association of vitamin D levels with unconventional biomarkers of kidney injury in patients with SCA. This is a cross-sectional, descriptive and analytical study carried out at the Hematology Service of the Hospital Universitário Walter Cantídio. Fifty-one adult patients diagnosed with SCA participated in the research. The control group consisted of 17 healthy adult individuals (HbAA) blood donors. SCA patients were stratified into 3 groups according to vitamin D levels, with or without the use of Hydroxyurea and in relation to the frequency of vaso-occlusive crises. Vitamin D deficiency was 13.72% of patients, while insufficiency in 31.37% and sufficiency in 54.91%. In addition, higher levels of vitamin D were observed in patients compared to the control group, with no influence from the use of HU. Urinary KIM-1 levels in patients were more than double those obtained in the control group. It is also noteworthy that there was a difference in the urinary levels of MCP-1, in which the patients had urinary concentrations of 160.69 pg / mL-Cr ± 202.61 while the control group 64.24 pg / mL-Cr ± 63, 47. There was an association between serum vitamin D levels and urinary levels of the KIM-1 biomarker, which can be observed a tendency to increase KIM-1 levels in patients with vitamin D deficiency. of sensitivity and specificity of the KIM- 1 and MCP-1 biomarkers. The result proved to be statistically significant for KIM-1 and MCP1, demonstrating that patients with sickle cell anemia and with low serum levels of vitamin D may have a 70% chance of developing kidney disease. It was concluded that there was no relationship between vitamin D deficiency and the use of HU, nor with the frequency of vessel occlusion crises. However, vitamin D deficiency was related to the unconventional biomarkers of kidney injury KIM-1 and MCP-1, in patients with SCA.